Antecedents of Audit Quality in the Malang Public Accounting Firms: Moderating Effect of Auditor Professional Ethics - Evi Ratna Dwi Yanti Tjabo; Adi Prasetyo; Agung Prasetyo Nugroho Wicaksono (Master of Accounting Universitas Trunojoyo Madura, 2022)
The study aims to provide evidence that competency, independence, and accountability influenced the audit quality with professional auditor ethics as moderating variable. The method used in this study is associative research with a quantitative approach. Data on the study is obtained by disseminating questionnaires directly to the auditors as respondents. The population in this study is the auditors who work in the public accounting firm (PAF). The sample in this study is the auditor who worked at the public accounting firm in Malang, with a total of 10 public accounting firms determined using sampling techniques. The data analysis technique in this study uses SmartPLS software 3.0. The results of these studies indicated that the auditor's competency and accountability significantly impacted the audit quality. Auditor's independence did not affect the quality of the audit. Moreover, the study also proved that professional auditor ethics could not moderate the influence of auditors' competency, independence, and accountability on audit quality. This suggests that professional auditor ethics is not essential in forming good audit quality, and auditors in the Malang public accounting firm need the training to enhance their capability in performing audit assignments.